Pembiayaan Pendidikan Tinggi dalam Rangka Efisiensi Internal di STKIP Kusuma Negara Jakarta - M Mahmud (LPPM STKIP Kusuma Negara, 2017)
This research was scintifically purposed to describe management of education finances in academic duty performancefor internal efficiency of STKIP Kusuma Neagara Jakarta. This research used descriptif methode by technique to collect the data’s interview is used for the rector, rector assistants and financial administration. The observation is done directly to find out the information and the result of interview. The study gives description about the management of education finances and the increasing academic duty performance under efficiency internal control It can be concluded that STKIP Kusuma Negara Jakarta has the increasing of academic duty performace in all of the sectors. And then realisation management of education finances the goal together in the university. Then also the rector in the arrangement for education finances are done quaranted all sectors of academic duty performance as well. The essay above can be found that the management of education finances to increase the academic duty performance for internal effiency in STKIP Kusuma Negara Jakarta that been realized to optimal.